Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/ijerph191911895
|View full text |Cite
|
Sign up to set email alerts
|

Diet and Systemic Lupus Erythematosus (SLE): From Supplementation to Intervention

Abstract: Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune inflammatory disease characterised by immune dysregulation affecting multiple organs. Current anti-inflammatory treatments used in SLE are associated with unwanted side-effects. Dietary supplementation has been suggested as a safe and effective addition to conventional treatment, but evidence of efficacy in SLE or preventing associated comorbidities is uncertain. Methods: We identified literature on clinical trials focused on nutritional in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 59 publications
0
11
0
1
Order By: Relevance
“…Although DII has been validated that it can reflect the dietary inflammation potential and systemic inflammation level, it is not designed for predicting hypertension ( 42 , 43 ). We aimed at screening dietary factors most related to the risk of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Although DII has been validated that it can reflect the dietary inflammation potential and systemic inflammation level, it is not designed for predicting hypertension ( 42 , 43 ). We aimed at screening dietary factors most related to the risk of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…One study in autoimmune, Lupus-prone mice suggested that fish oil (omega 3) inhibited production of pro-inflammatory cytokines and improved kidney injury ( 28 ), and omega-3 intake has been linked to improved outcomes in SLE patients, including reduced inflammation, disease activity, and oxidative stress ( 22 ). Other published work has shown that supplementation, such as with omega-3, can help reduce SLE-related sequelae ( 22 , 29 ) and disease activity ( 30 , 31 ) and that omega 3 may reduce the production of inflammatory markers, cytokines and CRP to improve inflammation ( 32–34 ). Finally, PUFA supplements, in particular omega-3, may be an effective treatment for non-specific dry eye disease ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Além dos exercícios físicos, mudanças no estilo de vida, como cessação do tabagismo e controle de peso, são importantes para o controle de fatores de risco cardiovasculares (MONTHIDA FANGTHAM et al, 2019). Outro importante adjuvante são os fatores dietéticos, como a restrição de gorduras, para melhor manutenção do peso e melhora na fadiga; o uso de vitaminas, como a vitamina D, que pode reduzir a inflamação e melhorar a saúde óssea; vitamina E, que pode regular a produção de anticorpos; e a suplementação de ômega-3, que reduz a atividade da doença, a inflamação e o estresse oxidativo (JIAO et al, 2022).…”
Section: Tratamento E Manejounclassified